v.2 - Jain, M.P. (Gurgaon, 2013)
The book is an exhaustive and analytical commentary on Indian constitutional law. This updated 6th edition covers the legislative changes made upto the Constitution (Ninety-eighth Amendment) Act, 2012 (w.e.f. 1 January 2013) and the latest essential case law from the Supreme Court of India and from various High Courts. It provides crucial documents, including the British constitutional documents starting from the Government of India Act, 1800, tracing the historical development of the Indian Constitution
Keywords: Constitutional law-India